The Bloomsbury reader in religion, sexuality, and gender - Boisvert, Donald L.; Daniel-Hughes, Carly (t & t clark, 2018)
"How do religion, gender and sexuality interact? How have they impacted, and continue to impact, human culture? The Bloomsbury Reader in Religion, Sexuality and Gender brings together, for the first time, the key texts in the field. Designed as a textbook for use in a classroom setting, it offers thought-provoking selections of some of the most compelling and timely readings available today. The Reader is divided into three parts (bodies; desires; performances). Each considers, from a thematic perspective, the ways in which people have made sense of their religious and sexual experiences, the ways they imagine and talk about gender, sex and the sacred, and the multiple meanings they ascribe to them. Traditions represented include indigenous spiritualities, Christianity, Judaism, Islam, Asian traditions and new religious movements. Some readings are more theoretical or historical in nature, thereby providing wide-ranging contexts for reflection and discussion. The reader includes extensive introductions to the book as a whole and to each of the three parts, as well as short paragraphs contextualizing each of the readings. Each section includes discussion questions for classroom use; additional readings and resources, as well as a glossary of key terms, are also provided. The Bloomsbury Reader in Religion, Sexuality and Gender is an ideal resource for courses on religion and sexuality, religion and gender, or religion and contemporary culture more generally."